2013
DOI: 10.1007/s12039-013-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial and larvicidal compounds of Toddalia asiatica root bark

Abstract: From the n-hexane, ethyl acetate and methanol extracts of Toddalia asiatica root bark were isolated eight compounds (1-8) which were identified on the basis of both spectroscopic and physical data as well as comparison with already published results. The crude extracts and isolated compounds showed moderate in vitro antiplasmodial activity against D6 (chloroquine-sensitive) and W2 (chloroquine-resistant) strains of Plasmodium falciparum. The extracts and isolates also exhibited larvicidal activities against Ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The roots and barks of T. asiatica have been used in Miao minority medicine, mainly in Guizhou, Yunnan, and Guangxi provinces in China, for the treatment of fall injuries, rheumatic arthralgia, stomachache, chronic lumbago, and diarrhea [3,4]. Previous phytochemical and pharmacological investigations of different parts of this plant revealed that coumarins are the main secondary metabolites [5], some of which exhibited cytotoxic, antimalarial [6], antiviral [7], anti-inflammatory [8], antibacterial [9], anti-platelet aggregation [10], anti-plasmodial, larvicidal [11], phosphodiesterase-4 inhibitory [12], and osteoclastogenesis activities [13]. Even though coumarins are rather studied, less attention has been paid to their glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…The roots and barks of T. asiatica have been used in Miao minority medicine, mainly in Guizhou, Yunnan, and Guangxi provinces in China, for the treatment of fall injuries, rheumatic arthralgia, stomachache, chronic lumbago, and diarrhea [3,4]. Previous phytochemical and pharmacological investigations of different parts of this plant revealed that coumarins are the main secondary metabolites [5], some of which exhibited cytotoxic, antimalarial [6], antiviral [7], anti-inflammatory [8], antibacterial [9], anti-platelet aggregation [10], anti-plasmodial, larvicidal [11], phosphodiesterase-4 inhibitory [12], and osteoclastogenesis activities [13]. Even though coumarins are rather studied, less attention has been paid to their glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…The Kani tribes use the extract of this plant to cure skin diseases (Ayyanar and Ignacimuthu 2005). The extracts of this plant exhibited strong insecticidal properties against Aedes aegypti Linnaeus, A. albopictus Skuse and Culex quinquefasciatus Say (Borah et al 2010;Liu et al 2013;Nyahanga et al 2013); and larvicidal and antifeedant properties against Helicoverpa armigera Hübner ( Sundararajan and Kumuthakalavalli 2001;Ramya et al 2009). H. armigera is a polyphagous pest causing serious damage to many agricultural and horticultural crops such as cotton, tomato, brinjal, chickpea, pigeonpea, chilli, maize, and sorghum (Manjunath et al 1989;Talekar et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated compounds from T. asiatica showed the highest level of larvicidal activity. Toddalia asiatica exhibited strong larvicidal effects against Aedes aegypti due to presence of sibricin and coumarins compounds [45]. Aqueous extract of Toddalia asiatica Lam.…”
Section: Larvicidal Activitymentioning
confidence: 99%